Perspective on completing natural inflation - Choi, Ki-Young; Kim, Jihn E.; Kyae, Bumseok (Frontiers in Physics, 2015)
We present a perspective on the inflation paths in 2-, 3-, …, N-flation models based on the ultraviolet completion in heterotic string theory, where a number of grand unification scale axions are used. The number of non-Abelian gauge groups for a natural inflation is restricted in string compactification, and we argue that the most plausible completion of natural inflation from a theory perspective is the 2– and 3–flation.